STUDY ON THE CONTENT OF SEDIMENT PARTICLES IN THE AIR AROUND TG. JIU TOWN - Ramona Violeta Cazalbașu; Camelia Căpăţînă (Fiabilitate şi Durabilitate)
One of the most important problems of the modern era is the air pollution. This phenomenon, highly complex, has become the focus of several international organizations since the consequences of air pollution are felt outside the country borders. By and large wecan speak of a regional pollution, which consists of atmospheric contamination by waste or by products liquids, solids gas, threatening the health of people, plants and animals or which can attack materials, reduce visibility and cause unpleasant odors. On a planetary scale, the elimination or accumulation in the atmosphere of certain products, leads to irreparable consequences on the planet's natural balance: ozone depletion and global warming of the atmosphere. This paper presents the study on the sedimentparticles in the air in Tg-Jiu. Determination of particulate matter from the air was done according to Standard no. 10195 / 75.Air purity.Determination of settled particles. In 2014 no exceeding of the maximum allowable concentration of sediment particles has been found in the four sampling points and in2015, out of a total of 60 measurements in four sampling points only one was above the maximum permissible concentration